2017
DOI: 10.1016/j.jngse.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of cyclic CH4 injection in liquid-rich shale reservoirs based on the experiments using different-diameter shale cores and crude oil

Abstract: In this paper, the potential to enhance oil recovery (EOR) by CH 4 gas injection in shale reservoirs is investigated through numerical analysis based on the experiments using different-diameter shale cores and crude oil. The cores used in these experiments had the same length of 2 inches and six different diameters of 1, 1.5, 2, 3, 3.5 and 4 inches. The crude oil from Wolfcamp was used to saturate the shale core plugs. A Gas Chromatography/Mass Spectrometer (GC/MS) instrument and Xcalibur software were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…They discovered that the higher number of cycles yields more efficient contact between the injected fluid and reservoir oil; nevertheless, they emphasized that extra cycles do not constantly enhance oil production. Li and Sheng (2017) also reported that the incremental produced oil decreased while the number of cycles increased (Li and Sheng, 2017). On the other hand, the incremental oil produced is not a direct function of soaking time in all cases.…”
Section: Introductionmentioning
confidence: 93%
“…They discovered that the higher number of cycles yields more efficient contact between the injected fluid and reservoir oil; nevertheless, they emphasized that extra cycles do not constantly enhance oil production. Li and Sheng (2017) also reported that the incremental produced oil decreased while the number of cycles increased (Li and Sheng, 2017). On the other hand, the incremental oil produced is not a direct function of soaking time in all cases.…”
Section: Introductionmentioning
confidence: 93%
“…Waterflooding has a poor sweep efficiency in shale reservoirs due to the ultralow reservoir permeability. , Gas will break through the hydraulic fractures, leading to a low sweep efficiency. Thus, the method of CO 2 huff-n-puff injection, using the same well as both the production and the injection well, was applied to enhance oil recovery. The method has been proven effective both in conventional oil reservoirs and in lab experimental tests of shale core samples. Using this method, the injected CO 2 penetrates the reservoir matrix and diffuses into the shale oil. Meanwhile, shale reservoir rock will adsorb and trap the CO 2 during this process.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we conducted a series of huff-n-puff experiments with different core sizes and found that the core with a larger diameter yielded a lower oil recovery . The oil recovery in lab experiments could reach 50– 60%, ,,,, whereas the oil recovery is still less than 20% in field scale production. ,,,, Thus, numerical simulation is needed to investigate the gas penetration in the field size. Field scale simulation has been discussed by many researchers, who have explored the effect of operating parameters on oil recovery including soaking time, injection rate, miscible condition, CO 2 diffusivity, and number of huff-n-puff cycles. ,,, ,, But few articles have discussed the CO 2 sweep volume in the reservoir and the mechanisms of CO 2 -shale oil action in the gas penetrated region.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Sheng measured the efficiency of shale oil recovery through laboratory experiments and numerical simulation of using methane HnP. 31 further explored the inuences of soaking time and consumption time on fracture-matrix shale reservoirs in huff and puff experiments using N 2 . 32 Li et al (2019) conducted experiments comparing the effect of N 2 and CO 2 on EOR performance, verifying the great potential of CO 2 in improving shale oil recovery.…”
Section: Introductionmentioning
confidence: 99%